Peningkatan keterampilan sosial siswa melalui model pembelajaran team games tournament dalam pembelajaran IPS kelas V sekolah dasar - Priska Ayu Pamungkas; Jenny Indrastoeti Siti Poerwanti; Joko Daryanto (Didaktika Dwija Indria, 2019)
The purpose of this study was to improve social skills in social studies learning through the Team Games Tournament model and implement Team Games Tournament in the social skills of V students in Setono Elementary School no.95. PTK is carried out in two cycles, namely planning, action, observation, and reflection. The research subjects were fifth grade students of SD Negeri Setono No.95, Laweyan, Surakarta in the Academic Year 2018/2019, which totaled 33 students. Data collection techniques using questionnaires, interviews, observation, and documentation. Data analysis techniques are data reduction, data presentation, and conclusion drawing. The validity of the data uses content validity, source triangulation and technical triangulation. the first cycle of communication aspect score 2.7 increased to 3.05 in the second cycle. Interaction aspects score 2.87 to 3.12 in cycle II. The collaboration score is 2.9 to 3.12 in cycle II. The implementation of TGT in improving social skills includes (a) Class Presentations; (B) group; (c) Games; (d) Tournaments; (e) group awards. It can be concluded that the TGT learning model improves students' social skills in social studies subjects in fifth grade students of SD Negeri Setono No.95 Laweyan, Surakarta in the 2018/2019 academic year.